2023
DOI: 10.1186/s12936-023-04628-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparing field-collected versus remotely-sensed variables to model malaria risk in the highlands of western Uganda

Brandon D. Hollingsworth,
Hilary Sandborn,
Emmanuel Baguma
et al.

Abstract: Background Malaria risk is not uniform across relatively small geographic areas, such as within a village. This heterogeneity in risk is associated with factors including demographic characteristics, individual behaviours, home construction, and environmental conditions, the importance of which varies by setting, making prediction difficult. This study attempted to compare the ability of statistical models to predict malaria risk at the household level using either (i) free easily-obtained remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Most of the regions with very low and low transmission are located in the central, northeastern, and southwestern parts surrounded on both sides by moderate transmission regions and high malaria transmission in the northwestern, southern, and western parts [10]. Previous studies have shown that the transmission of malaria is influenced by various factors including the types of mosquito vectors, environmental conditions, and human-related factors like age, sex, immunity, and level of education [11][12][13].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Most of the regions with very low and low transmission are located in the central, northeastern, and southwestern parts surrounded on both sides by moderate transmission regions and high malaria transmission in the northwestern, southern, and western parts [10]. Previous studies have shown that the transmission of malaria is influenced by various factors including the types of mosquito vectors, environmental conditions, and human-related factors like age, sex, immunity, and level of education [11][12][13].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%